Combined supramolecular adhesives that are resistant to ultra-low temperatures and organic solvents

Combined supramolecular adhesives prepared by combining imidazole-based ionic liquids with phenol-containing compounds, the existing adhesives have been solved in terms of insufficient performance in terms of adhesive strength, low temperature resistance, solvent-resistant media and number of cycles, and high strength, good tolerance and recyclable effects have been achieved.

CN116285829BActive Publication Date: 2025-04-25SHAANXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310347982.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-04-25
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

The performance of existing combined supramolecular adhesives in terms of bonding strength, low temperature resistance, solvent resistance media and number of cycles has not yet met the requirements of practical application, and there is a lack of universal combination strategies in preparation.

Method used

By combining an imidazole-based ionic liquid with a phenol-containing compound, a combined supramolecular adhesive is prepared by grinding, melting or precipitation, with a mass ratio of the adhesive ranging from 1:15 to 15:1, preferably from 1:3 to 3:1.

Benefits of technology

The high strength of the adhesive, good ultra-low temperature tolerance, tolerance to organic solvents and recyclable properties are achieved, and the preparation steps are simple and the raw materials are cheap and easy to obtain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116285829B_ABST
    Figure CN116285829B_ABST
Patent Text Reader

Abstract

The invention discloses a combined supramolecular adhesive which is resistant to ultra-low temperature and organic solvents. The adhesive is prepared by grinding, melting or precipitation of an imidazole ionic liquid and a compound containing a phenol structure. The viscosity of the adhesive decreases with increasing temperature and increases with decreasing temperature. After cold and hot cycles, efficient interface bonding of materials such as metal, wood, glass, polytetrafluoroethylene and the like can be achieved. Reversible interface bonding can be achieved by cold and hot methods. Interface bonding residues can be dissolved by alcohol polar solvents such as ethanol to achieve on-demand separation. The adhesive can be used for multiple cycles without obvious attenuation under specific organic solvents, or low temperature, or ultra-low temperature conditions. Interface bonding can be stably maintained for a long time in ultra-low temperatures (such as liquid nitrogen) or in a variety of organic solvents, and the bonding strength has no obvious attenuation during the process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface interface chemistry and interface bonding, and in particular relates to a combined supramolecular adhesive suitable for use in ultra-low temperature and organic solvent environments. Background Art

[0002] Adhesive is a substance that can bond two or more components or materials together through interfacial adhesion and cohesion. Using adhesives for interfacial bonding can bond two identical or different objects together through close interfacial contact, so that mechanical force or function is transmitted through the interface. There are many types of adhesives, and the classification methods are also different. There is no universally recognized classification. In general, the classification can be based on the chemical properties of the adhesive, the physical state of the adhesive, the chemical composition of the main constituent units of the adhesive, the application mode of the adhesive to achieve effective bonding, the load-bearing function of the adhesive bonding strength, and the size of the adhesive molecule. According to the chemical composition of adhesives, they can be divided into two categories: organic and inorganic adhesives [Chem. Rev., 2021, 121, 11336-11384; Adv. Mater. Technol., 2019, 4, 1900193; Adv. Funct. Mater., 2020, 30, 1901693; J. Adhes. Sci. Technol., 2020, 34, 1269-1282; J. Am. Chem. Soc., 2020, 142, 5371-5379]; according to the physical state of adhesives at room temperature, they can be divided into liquid adhesives, paste adhesives, film adhesives and powder particle adhesives [Adv. Funct. Mater., 2020, 30, 1901693; The Vacuum Society of Japan, 1976, 19, 129-135]; According to the load stress that the adhesive can bear, it can be divided into structural adhesives and non-structural adhesives; According to the chemical composition of the adhesive, it can be divided into epoxy resin adhesives, polyurethane adhesives, polyvinyl acetate adhesives and silicone adhesives, etc. [Angew. Chem. Int. Ed., 2013, 52, 9422-9441; Appl. Therm. Eng., 2014, 66, 493-498; J. Ind. Eng. Ch em.,2015,29,1-11;Appl.Surf.Sci.,2019,479,1148-1160】;According to the use of adhesives, they can be divided into thermoplastic adhesives, thermosetting adhesives, light-curing adhesives and pressure-sensitive adhesives, etc. [Adv.Funct.Mater.,2019,30,1900998;J.Appl.Polym.Sci.,2015,132,41444;Polymers,2018,10,975;Reviews of Adhesion and Adhesives,2017,5,105-161;J.Therm.Anal.Calorim.,2022,147,7719-7727;Polymers,2018,10,1016;J.Appl.Polym. Sci., 2015, 132, 41444; Polym. Bull., 2018, 75, 1141-1147]; According to the size of the adhesive molecule, it can be divided into macromolecular (polymer or polymer) adhesives and small molecule adhesives [Chem. Soc. Rev., 2019, 48, 2682-2697; J. Mater. Chem. B, 2014, 2, 8110-8115; Angew. Chem. Int. Ed., 2013, 52, 3140-3144; Chem .Sci., 2014, 5, 3261-3266; Sci. Adv., 2017; 3, eaao0900; J. Am. Chem. Soc., 2019, 141, 8058-8063; J. Am. Chem. Soc., 2020, 142, 21522-21529; ACS Appl. Mater. Interfaces, 2020, 12, 38700-38707; J. Am. Chem. Soc., 2020, 142, 5371-5379]. Compared with the commonly studied polymer adhesives, supramolecular binders have developed slowly because supramolecular effects are easily affected by the environment. However, supramolecular binders have unique advantages in explaining and studying supramolecular interactions between adhesive components and interactions between adhesives and substrates because the molecular structure of the combined units is relatively easy to determine. In addition, the molecular structure of the component units of supramolecular adhesives can be precisely controlled, which is convenient for optimizing and updating the performance of adhesives. In recent years, some important research progress has been made in the field of combined supramolecular adhesives, which confirms that this type of adhesive is expected to achieve breakthroughs in environmental tolerance and is a type of adhesive with broad application prospects (J.Am.Chem.Soc.2020,142,21522; Biomacromolecules 2017,18,3524; Mater.Horiz.2022,9,700; J.Am.Chem.Soc.2020,142,5371; Angew.Chem.Int.Ed.2020,59,11871; CCS Chem.2020,2,1690; Adv.Funct.Mater.2010,20,1803). However, the bonding strength of combined supramolecular adhesives is generally lower than that of polymer adhesives [Biomacromolecules, 2017, 18, 3524-3530; Adv. Funct. Mater., 2018, 28, 1800599; Angew. Chem. Int. Ed.,2017,56,8731-8735], the performance in terms of low temperature resistance, solvent resistance and number of cycles is still far from practical application, and cannot be compared with polymer adhesives. In particular, the existing supramolecular adhesives have not formed a combination strategy with certain universality in preparation. Therefore, it is of great practical significance to invent a new universal preparation strategy for combined supramolecular adhesives and develop one or several types of supramolecular adhesives with long-lasting, high-strength bonding strength, universal substrate applicability, high-efficiency low temperature tolerance, high-efficiency solvent tolerance and recyclable properties. . Summary of the invention

[0003] The purpose of the present invention is to provide a type of combined supramolecular adhesive which can be peeled on demand, is resistant to organic solvents and is resistant to ultra-low temperatures.

[0004] For the above purpose, the combined supramolecular adhesive used in the present invention is prepared by grinding, melting or precipitation of an imidazolium ionic liquid and a compound containing a phenol structure; the imidazolium ionic liquid is composed of an imidazolium ion and its corresponding anion, the nitrogen atom of the imidazolium ion is connected to an alkyl chain, an alkoxy chain, an alkyl chain with a hydroxyl or amino group at the end, and an alkoxy chain with a hydroxyl or amino group at the end, and the anion is Cl - Br - PF6 - 、BF4 - 、NO3 - CF3SO3 - TFSI - Any one of .

[0005] Furthermore, the imidazole ionic liquid is any one of the following structural formulas:

[0006]

[0007]

[0008] The above-mentioned compound containing a phenol structure is any one of phenol, catechol, resorcinol, hydroquinone, pyrogallol, methyl gallate, 3-ethoxyphenol, 2,4-dimethylphenol, 2,6-dimethoxyphenol, 3-hydroxy-4-methoxytoluene, 2,6-dimethylphenol, 4-(1-hydroxyethyl)phenol, 2-ethylphenol, 3-ethylphenol, 2-methoxyhydroquinone, 4-methylresorcinol, 4-ethylresorcinol, toluene, 2-methylresorcinol, 3-methylcatechol, 5-methylresorcinol, 5-methoxyresorcinol, 4-methylcatechol, 3-methoxycatechol, p-tert-butylcatechol, 2,6-dihydroxyacetophenone, dopamine, caffeic acid, dihydrocaffeic acid, tetramethylhydroquinone, hexahydroxybenzene, tannic acid, tea polyphenols, catechins, etc.

[0009] The above method for preparing the adhesive by precipitation is: dissolving the imidazole ionic liquid and the compound containing a phenol structure in ultrapure water respectively, then mixing the two solutions evenly to produce a precipitate, and centrifuging and separating the precipitate to obtain the adhesive.

[0010] In the above adhesive, the mass ratio of the imidazole ionic liquid to the compound containing a phenol structure is 1:15 to 15:1, and preferably the mass ratio of the imidazole ionic liquid to the compound containing a phenol structure is 1:3 to 3:1.

[0011] Compared with the prior art, the present invention has the following beneficial effects:

[0012] (1) The adhesive of the present invention has simple synthesis steps and the raw materials are cheap and readily available; the components of the adhesive are non-sticky and can be stored stably for a long time; the adhesive material can be obtained after mixing, and can be prepared on demand at any time;

[0013] (2) The adhesive of the present invention has good wettability and is green and environmentally friendly. It is a viscoelastic fluid with viscosity as the dominant property at room temperature or high temperature and has good general applicability. It exhibits good bonding effect on various materials such as stainless steel, iron, copper, aluminum, glass, wood, polytetrafluoroethylene, etc. The bonding and separation can be controlled by temperature, and the adhesive remaining on the joint after release can be easily removed by ethanol solvent. The bonded samples can be separated as needed by heating or washing with ethanol solution. The separated samples can be bonded again without adding adhesive, and the number of cycles is large without obvious attenuation of bonding strength.

[0014] (3) The adhesive of the present invention can withstand organic solvents. The samples bonded by the adhesive have no obvious attenuation of bonding strength after being immersed in various solvents such as petroleum ether, n-hexane, toluene, anhydrous ether, dichloromethane, tetrahydrofuran, ethyl acetate, acetone, acetonitrile, water and seawater for a long time. The samples can be loaded with heavy objects and immersed for several months without falling off.

[0015] (4) The adhesive of the present invention has good ultra-low temperature tolerance and maintains good stability in liquid gases such as liquid nitrogen. There is no obvious attenuation of its bonding strength when stored in a liquid nitrogen environment. It has potential application value in interfacial bonding in ultra-low temperature environments such as liquefied natural gas (-163°C), liquid nitrogen (-196°C) and in organic solvent systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the thermogravimetric graph of adhesive P1 in Example 1.

[0017] Figure 2 Graph showing the changes in G′ and G″ of adhesive P1 in Example 1 as a function of temperature cycle.

[0018] Figure 3 Graph showing the change in complex viscosity of adhesive P1 in Example 1 as a function of temperature cycle.

[0019] Figure 4 is the thermogravimetric graph of adhesive P2 in Example 2.

[0020] Figure 5 Graph showing the changes in G′ and G″ of adhesive P2 in Example 2 as a function of temperature cycle.

[0021] Figure 6 This is a graph showing the change in complex viscosity of adhesive P2 in Example 2 as a function of temperature cycles.

[0022] Figure 7 is the thermogravimetric graph of adhesive P3 in Example 3.

[0023] Figure 8 Graph showing the changes of G′ and G″ of adhesive P3 in Example 3 with temperature cycles.

[0024] Fig. 9 This is a graph showing how the composite viscosity of adhesive P3 in Example 3 changes with temperature cycles.

[0025] Fig.10 is the thermogravimetric graph of adhesive P4 in Example 4.

[0026] Fig.11 Graph showing the variation of G′ and G″ of adhesive P4 in Example 4 with temperature cycles.

[0027] Fig.12 This is a graph showing the change in complex viscosity of adhesive P4 in Example 4 as a function of temperature cycles.

[0028] Fig.13 is the thermogravimetric graph of adhesive P1w in Example 5.

[0029] Fig.14 Graph showing the variation of G′ and G″ of adhesive P1w in Example 5 with temperature cycles.

[0030] Fig.15 This is a graph showing the change in complex viscosity of adhesive P1w in Example 5 as a function of temperature cycle.

[0031] Fig.16 is the thermogravimetric graph of adhesive P2w in Example 6.

[0032] Fig.17 Graph showing the variation of G′ and G″ of adhesive P2w in Example 6 with temperature cycles.

[0033] Fig.18 This is a graph showing the change in complex viscosity of adhesive P2w in Example 6 as a function of temperature cycle.

[0034] Fig.19 This is a digital photo showing the universal application of heavy objects on the adhesive P1 substrate in Example 1.

[0035] Fig. 20 This is a digital photo showing the universal use of adhesive P1w substrate for hanging heavy objects in Example 5.

[0036] Fig.21 This is a digital photograph showing the solvent resistance of adhesive P1w in Example 5 hanging a heavy object.

[0037] Fig. 22 This is a digital photograph of the ultra-low temperature resistance of adhesive P1w in Example 5. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0039] The structural formula of the imidazole ionic liquid used in the following examples is as follows:

[0040]

[0041]

[0042] Example 1

[0043] 3g of the imidazole ionic liquid of formula I-1 and 2g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P1). Figure 1 It can be seen that the thermal analysis decomposition temperature of adhesive P1 is ≥300°C, and its storage modulus (G') is smaller than the loss modulus (G") (see Figure 2 ), macroscopically it behaves as a liquid; its rheological properties are temperature-dependent, the higher the temperature, the greater the fluidity, and the rheological properties are reversible between room temperature and low temperature (see Figure 3 ).

[0044] Example 2

[0045] 3g of the imidazole ionic liquid of formula I-2 and 2.4g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P2). Figure 4 It can be seen that the thermal analysis decomposition temperature of adhesive P2 is ≥300°C, and its storage modulus (G') is smaller than the loss modulus (G") (see Figure 5 ), macroscopically it behaves as a liquid; its rheological properties are temperature-dependent, the higher the temperature, the greater the fluidity, and the rheological properties are reversible between room temperature and low temperature (see Figure 6 ).

[0046] Example 3

[0047] 3g of the imidazole ionic liquid of formula I-3 and 3.75g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P3). Figure 7 It can be seen that the thermal analysis decomposition temperature of adhesive P3 is ≥300°C, and its storage modulus (G') is smaller than the loss modulus (G") (see Figure 8 ), macroscopically it behaves as a liquid; its rheological properties are temperature-dependent, the higher the temperature, the greater the fluidity, and the rheological properties are reversible between room temperature and low temperature (see Fig. 9 ).

[0048] Example 4

[0049] 3g of the imidazole ionic liquid of formula I-4 and 4.5g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P4). Fig.10 It can be seen that the thermal analysis decomposition temperature of adhesive P4 is ≥300°C, and its storage modulus (G') is smaller than the loss modulus (G") (see Fig.11 ), macroscopically it behaves as a liquid; its rheological properties are temperature-dependent, the higher the temperature, the greater the fluidity, and the rheological properties are reversible between room temperature and low temperature (see Fig.12 ).

[0050] Example 5

[0051] 3g of the imidazole ionic liquid of formula I-1 and 2g of tannic acid were placed in a 25mL beaker, and dissolved in 10mL of ultrapure water, and then the aqueous solution of formula II-1 was slowly poured into the aqueous solution of formula I-1. After thorough mixing, a translucent paste-like viscous precipitate was generated, and centrifuged to separate the precipitate, which was the supramolecular adhesive (denoted as P1w). Fig.13 It can be seen that the thermal analysis decomposition temperature of adhesive P1w is ≥300°C, and its storage modulus (G') is smaller than the loss modulus (G") (see Fig.14 ), macroscopically it behaves as a liquid; its rheological properties are temperature-dependent, the higher the temperature, the greater the fluidity, and the rheological properties are reversible between room temperature and low temperature (see Fig.15 ).

[0052] Example 6

[0053] 3g of the imidazole ionic liquid of formula I-2 and 2.4g of tannic acid were placed in a 25mL beaker, and dissolved in 10mL of ultrapure water, and then the aqueous solution of formula II-1 was slowly poured into the aqueous solution of formula I-2. After thorough mixing, a translucent paste-like viscous precipitate was generated, and centrifuged to separate the precipitate, which was the supramolecular adhesive (denoted as P2w). Fig.16 It can be seen that the thermal analysis decomposition temperature of adhesive P2w is ≥300°C, and its storage modulus (G') is smaller than the loss modulus (G") (see Fig.17 ), macroscopically it behaves as a liquid; its rheological properties are temperature-dependent, the higher the temperature, the greater the fluidity, and the rheological properties are reversible between room temperature and low temperature (see Fig.18 ).

[0054] Example 7

[0055] 3 g of the imidazole ionic liquid represented by formula I-5 and 2 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P1-1).

[0056] Example 8

[0057] 3 g of the imidazole ionic liquid represented by formula I-6 and 2 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P1-2).

[0058] Example 9

[0059] 3 g of the imidazole ionic liquid represented by formula I-1 and 3 g of methyl gallate were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P5).

[0060] Example 10

[0061] 3 g of the imidazole ionic liquid represented by formula I-1 and 3 g of pyrogallol were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P6).

[0062] Embodiment 11

[0063] 3 g of the imidazole ionic liquid represented by formula I-1 and 3 g of catechol were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P7).

[0064] Example 12

[0065] 3 g of the imidazole ionic liquid represented by formula I-1 and 3 g of resorcinol were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P8).

[0066] Example 13

[0067] 3 g of the imidazole ionic liquid represented by formula I-1 and 3 g of phenol were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P9).

[0068] Embodiment 14

[0069] 3 g of the imidazole ionic liquid represented by formula I-7 and 2 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P10).

[0070] Embodiment 15

[0071] 3 g of the imidazole ionic liquid represented by formula I-8 and 2 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P11).

[0072] Example 16

[0073] 3 g of the imidazole ionic liquid represented by formula I-9 and 2 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P12).

[0074] Embodiment 17

[0075] 3 g of the imidazole ionic liquid represented by formula I-10 and 2.4 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P13).

[0076] Embodiment 18

[0077] 3 g of the imidazole ionic liquid represented by formula I-11 and 2.4 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P14).

[0078] Embodiment 19

[0079] 3 g of the imidazole ionic liquid represented by formula I-12 and 2.4 g (1.41 mmol) of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P15).

[0080] Embodiment 20

[0081] 3 g of the imidazole ionic liquid represented by formula I-13 and 3.75 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P16).

[0082] Embodiment 21

[0083] 3 g of the imidazole ionic liquid represented by formula I-14 and 3.75 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P17).

[0084] Embodiment 22

[0085] 3 g of the imidazole ionic liquid represented by formula I-15 and 3.75 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P18).

[0086] Embodiment 23

[0087] 3 g of the imidazole ionic liquid represented by formula I-16 and 3.75 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P19).

[0088] Embodiment 24

[0089] 3 g of the imidazole ionic liquid represented by formula I-17 and 3.75 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which was a supramolecular adhesive (denoted as P20).

[0090] Embodiment 25

[0091] 3 g of the imidazole ionic liquid represented by formula I-18 and 3.75 g of tannic acid were fully ground to obtain a translucent paste-like viscous substance, which is a supramolecular adhesive (denoted as P21).

[0092] In order to accurately test the bonding strength of the adhesive of the present invention, the sample interface bonding process includes the following steps: pretreatment before bonding, that is, wiping the surfaces of the two bonded samples clean to avoid the adverse effects of impurities such as water stains and dust on the interface bonding, marking the customized sample at 10mm away from the edge (the side away from the through hole) as the overlapping edge of the single lap joint, the bonding area is fixed to 20mm×10mm, and a certain amount of adhesive is carried with a scraper and evenly coated on the surface of the bonding area. Two samples coated with adhesive are placed in an oven at 160°C. After heating for 20 minutes, the bonding areas of the two samples are overlapped in the form of a single lap joint while hot, and the air in the bonding area is driven away to fully fit, and a certain pressure is applied to ensure that the two samples are tightly combined. After waiting for 20 minutes, cool to room temperature to complete the interface bonding. The bonding strength test is completed on a universal testing machine, and the test method is a single lap shear test mode. During the test, the sample was stretched in two opposite directions parallel to the bonding surface at a stretching rate of 20 mm / min. The peak value of the stress F (N) at the moment of pulling apart was tested. The stress per unit bonding area was calculated according to formula (1), which is the bonding strength of the sample.

[0093] T = F / S (1)

[0094] Where F is the peak stress at the moment of pulling apart, in N; S is the bonding area, in mm 2; T is the lap shear strength, in MPa. According to the above steps, adhesives P1, P2, P3, P4, P1w, P2w, P1-1 and P1-2 are used to bond 200mm 2 The bonding strength and average bonding strength of samples made of 304 stainless steel, copper, aluminum, iron, pine wood and tempered glass after five tests are shown in Tables 1 to 8. P5, P6, P7, P8 and P9 are bonded to 200mm 2 The bonding strength and average bonding strength of the 304 stainless steel samples tested for three times are shown in Table 9. Adhesives P10 to P21 bonded 200 mm 2 The bonding strength and average bonding strength of samples made of 304 stainless steel, copper, aluminum, iron, pine wood and tempered glass after 5 tests are shown in Tables 10 to 21.

[0095] Table 1 Adhesion strength of adhesive P1 to various substrates (MPa)

[0096]

[0097] Table 2 Adhesion strength of adhesive P2 to various substrates (MPa)

[0098]

[0099]

[0100] Table 3 Adhesion strength of adhesive P3 to various substrates (MPa)

[0101]

[0102] Table 4 Adhesion strength of adhesive P4 to various substrates (MPa)

[0103]

[0104] Table 5 Adhesion strength of adhesive P1w to various substrates (MPa)

[0105]

[0106]

[0107] Table 6 Adhesion strength of adhesive P2w to various substrates (MPa)

[0108]

[0109] Table 7 Adhesion strength of adhesive P1-1 to various substrates (MPa)

[0110]

[0111] Table 8 Adhesion strength of adhesive P1-2 to various substrates (MPa)

[0112]

[0113]

[0114] Table 9 Adhesion strength of adhesives P5, P6, P7, P8 and P9 to 304 stainless steel substrate (MPa)

[0115]

[0116] Table 10 Adhesion strength of adhesive P10 to various substrates (MPa)

[0117]

[0118] Table 11 Adhesion strength of adhesive P11 to various substrates (MPa)

[0119]

[0120]

[0121] Table 12 Adhesion strength of adhesive P12 to various substrates (MPa)

[0122]

[0123] Table 13 Adhesion strength of adhesive P13 to various substrates (MPa)

[0124]

[0125] Table 14 Adhesion strength of adhesive P14 to various substrates (MPa)

[0126]

[0127] Table 15 Adhesion strength of adhesive P15 to various substrates (MPa)

[0128]

[0129] Table 16 Adhesion strength of adhesive P16 to various substrates (MPa)

[0130]

[0131] Table 17 Adhesion strength of adhesive P17 to various substrates (MPa)

[0132]

[0133] Table 18 Adhesion strength of adhesive P18 to various substrates (MPa)

[0134]

[0135] Table 19 Adhesion strength of adhesive P19 to various substrates (MPa)

[0136]

[0137] Table 20 Adhesion strength of adhesive P20 to various substrates (MPa)

[0138]

[0139] Table 21 Adhesion strength of adhesive P21 to various substrates (MPa)

[0140]

[0141] The experimental results show that the adhesive P1 obtained in Example 1 can be used to bond 200 mm 2 The samples are made of 304 stainless steel, copper, aluminum, iron, pine wood and glass. They can carry 50kg of weight. The actual picture is as follows Fig.19 Adhesive P1w obtained in Example 5 was used to bond 200 mm 2 The samples are made of 304 stainless steel, copper, aluminum, iron, pine wood and glass. They can carry 40kg of weight. The actual picture is as follows Fig. 20 The adhesive P1 obtained in Example 1 was further bonded to 200 mm 2 For the 304 stainless steel sample, the adhesive remaining on the matrix after separation can be bonded again after heating, and its bonding strength has no obvious attenuation compared with the first bonding. This cycle can be repeated at least 10 times. The bonding strength test results of each bonding are shown in Table 22.

[0142] Adhesives P1 and P1w obtained in Example 1 and Example 5 were used to bond 200 mm thick 2 The 304 stainless steel samples were immersed in different solvents such as petroleum ether, n-hexane, toluene, anhydrous ether, dichloromethane (DCM), tetrahydrofuran (THF), ethyl acetate (EA), acetone, acetonitrile, water and seawater for 60 days. The bonding strength and average bonding strength of the five tests are shown in Tables 23 and 24.

[0143] Table 22 Adhesion strength of adhesive P1 during multiple bonding cycles (MPa)

[0144]

[0145] Table 23 Adhesion strength of adhesive P1 after immersion in various solvents for 60 days (MPa)

[0146]

[0147] Table 24 Adhesion strength of adhesive P1w after immersion in various solvents for 60 days (MPa)

[0148]

[0149] Adhesive P1w obtained in Example 5 was used to bond 200 mm 2 The 304 stainless steel sample was loaded with a 2.0kg weight and immersed in solvents such as petroleum ether, n-hexane, toluene, anhydrous ether, dichloromethane, tetrahydrofuran, ethyl acetate, acetone, acetonitrile, water and seawater. The results showed that it lasted for more than two months without falling off. The actual picture is as follows Fig.21 shown.

[0150] The adhesives P1 and P1w obtained in Example 1 and Example 5 were respectively bonded to 200 mm 2 The 304 stainless steel samples were immersed in liquid nitrogen for 1 to 7 days, and their bonding strength decayed, but they still maintained high-strength bonding performance. The test results are shown in Tables 25 and 26.

[0151] Table 25 Adhesion strength of adhesive P1 after immersion in liquid nitrogen (-196°C) (MPa)

[0152]

[0153]

[0154] Table 26 Adhesion strength of adhesive P1w after immersion in liquid nitrogen (-196°C) (MPa)

[0155]

[0156] The adhesive P1w obtained in Example 5 was bonded to 200 mm 2 The 304 stainless steel sample is loaded with a 2.0kg weight and immersed in liquid nitrogen until the liquid nitrogen evaporates completely and the sample returns to room temperature. The sample will not fall off during the whole process. The actual picture is as follows Fig. 22 shown.

[0157] Based on the above experimental results, it can be seen that adhesives P2, P3, P4, P1w, P2w, P1-1 and P1-2 have the same properties as adhesive P1, and show good bonding effects on various materials such as 304 stainless steel, copper, aluminum, iron, pine wood, glass, polytetrafluoroethylene, etc.; bonding and separation can be controlled by temperature, and the adhesive remaining on the joint after release can be easily removed by ethanol; the bonded samples can be separated on demand after heating or washing with ethanol solution, and the separated samples can be bonded again without adding adhesive, with a large number of cycles and no obvious attenuation of bonding strength; they can tolerate organic solvents, and the bonding strength of the samples bonded by them does not show obvious attenuation after being immersed in various organic and inorganic solvents such as petroleum ether, n-hexane, toluene, anhydrous ether, dichloromethane, tetrahydrofuran, ethyl acetate, acetone, acetonitrile, water and seawater for a long time, and they do not fall off when immersed for several months while carrying heavy objects; they have good ultra-low temperature tolerance, maintain good stability in liquid gases such as liquid nitrogen, and their bonding strength does not show obvious attenuation when stored in a liquid nitrogen environment.

Claims

1. A combined supramolecular adhesive that is resistant to ultra-low temperatures and organic solvents, characterized in that: The adhesive is prepared by grinding, melting or precipitation of an imidazole ionic liquid and a compound containing a phenol structure; The imidazolium ionic liquid is composed of an imidazolium ion and its corresponding anion, wherein the nitrogen atom of the imidazolium ion is connected to an alkyl chain, an alkoxy chain, an alkyl chain with a hydroxyl or amino terminal, or an alkoxy chain with a hydroxyl or amino terminal, and the anion is Cl - Br - PF6 - 、BF4 - 、NO3 - CF3SO3 - TFSI - Any one of .

2. The combined supramolecular adhesive resistant to ultra-low temperature and organic solvents according to claim 1, characterized in that The imidazole ionic liquid is any one of the following structural formulas: 。 3. The combined supramolecular adhesive capable of resisting ultra-low temperature and organic solvents according to claim 1, characterized in that: The compound containing a phenol structure is any one of phenol, catechol, resorcinol, hydroquinone, pyrogallol, methyl gallate, 3-ethoxyphenol, 2,4-dimethylphenol, 2,6-dimethoxyphenol, 3-hydroxy-4-methoxytoluene, 2,6-dimethylphenol, 4-(1-hydroxyethyl)phenol, 2-ethylphenol, 3-ethylphenol, 2-methoxyhydroquinone, 4-methylresorcinol, 4-ethylresorcinol, 2-methylresorcinol, 3-methylcatechol, 5-methylresorcinol, 5-methoxyresorcinol, 4-methylcatechol, 3-methoxycatechol, p-tert-butylcatechol, 2,6-dihydroxyacetophenone, dopamine, caffeic acid, dihydrocaffeic acid, tetramethylhydroquinone, hexahydroxybenzene, tannic acid, tea polyphenols, and catechins.

4. The combined supramolecular adhesive capable of resisting both ultra-low temperature and organic solvent according to claim 1, characterized in that: The method for preparing the adhesive by precipitation is as follows: dissolving the imidazole ionic liquid and the compound containing the phenol structure in ultrapure water respectively, then mixing the two solutions evenly to produce a precipitate, and centrifuging and separating the precipitate to obtain the adhesive.

5. The combined supramolecular adhesive capable of resisting ultralow temperature and organic solvents according to any one of claims 1 to 4, characterized in that: The mass ratio of the imidazole ionic liquid to the compound containing a phenol structure is 1:15 to 15:

1.

6. The combined supramolecular adhesive capable of resisting ultra-low temperature and organic solvents according to claim 5, characterized in that: The mass ratio of the imidazole ionic liquid to the compound containing a phenol structure is 1:3 to 3:1.